Application of Portulaca oleracea L. Extract as a Biostimulant with Several Types of Solvents on The Growth of Kale (Brassica oleracea var. achepala) - Cleopatra; Zozy Aneloi Noli; M. Idris; Chairul; Suwirmen; Solfiyeni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Plant extracts are one biostimulant sources that have the potential to increase plant growth and yield. Portulaca contains secondary metabolites, macro and micronutrients, and amino acids, which have the potential as biostimulants. The research aims to determine the best type of solvent in the Portulaca extraction process as a biostimulant. The method used in this study was a Completely Randomized Design (CRD) with three treatments (aquadest, ethanol, and methanol) and nine replicates. The application of Portulaca extract extracted with several solvents significantly affected root length parameters of kale, with the most extended the root length of 15.80 cm. However, it did not have a significantly different effect on other parameters. Based on the proximate analysis, Portulaca extract extracted with ethanol solvent produces a protein content of 25.26%.